PENGEMBANGAN MODUL DIGITAL TENTANG PERISTIWA G30S/PKI UNTUK MENINGKATKAN MINAT BELAJAR DAN BERPIKIR KRITIS SISWA - Eki Robbi Kusuma (Universitas Negeri Malang, 2022)
This study aims to develop teaching materials in the form of modules with the latest media, namely digital books with G30S/PKI materials to increase students' interest in learning and critical thinking skills. This research is a type of R&D research that uses the Borg & Gall development procedure which was modified by Sukmadinata into 3 main stages. The subjects in this development research were students in grade XII at MAN 1 Pasuruan. The instrument for collecting feasibility data was in the form of a questionnaire of material experts, media experts, students, and teachers. The instrument for testing students' interest in learning is using student questionnaires and critical thinking skills using pre-test and post-test. The results of the research on the development of this digital module are as follows. First, the scores of material experts, media experts, teachers, and small and large group tests get a very decent predicate. Second, the testing of students’ interest in the experimental class before and after being given a digital module increased by 25.10 percent. Lastly, the pre-test and post-test of the experimental class increased by an average of 32.59 percent. Penelitian ini bertujuan untuk mengembangkan bahan ajar berupa modul dengan media terkini yakni buku digital dengan materi G30S/PKI untuk meningkatkan minat belajar dan kemampuan berpikir kritis siswa. Penelitian ini merupakan jenis penelitian R&D yang menggunakan prosedur pengembangan Borg & Gall yang dimodifikasi oleh Sukmadinata menjadi tiga tahap utama. Subjek dalam penelitian pengembangan ini adalah siswa kelas XII di MAN 1 Pasuruan. Instrumen pengumpulan data kelayakan berupa angket ahli materi, ahli media, siswa, dan guru. Intrumen pengujian minat belajar siswa menggunakan angket siswa dan kemampuan berpikir kritis menggunakan pre-test dan post-tes. Hasil penelitian pengembangan modul digital ini sebagaimana berikut. Pertama, skor ahli materi, ahli media, guru, uji kelompok kecil dan besar mendapatkan prediket sangat layak. Kedua, Pengujian minat kelas eksperimen sebelum dan sesudah diberikan modul digital meningkat 25.10 persen. Terakhir, pengujian pre-test dan post-test kelas eksperimen meningkat rerata 32.59 percent